THEORETICAL AND PROBABILITY APPROACH TO THE ASSESSMENT OF THE LEVEL OF GRAIN DAMAGE DURING TRANSPORTATION - Ivanov О. М.; Simonov, K. V. (Scientific Progress & Innovations, 2021)
Grain is a key food resource that shapes the food security of the state and is a valuable raw material for manufacturing a large number of food products. In addition, grain is a profitable commodity for sale in domestic and foreign markets with high economic benefits. Due to the limited area for crops cultivation and the growing demand for grain, there is a need to increase the level of grain yields. The key guarantee of obtaining a significant gross grain harvest is the use of high quality seed material. Leading breeders and scientists have found that 50 % of received high yields depend on seed quality. Seed quality depends not only on the programmed grain genetic potential, but the integrity of the grain structure with no mechanical dam-age is equally important. Thus, according to practical studies, the use of a single scraper conveyor to move grain can cause almost 10 % in the grain flow. Since the number of elevating machines on one production line can range from one to tens, the amount of damaged grain is quite large. The aim of the work was to provide the method for assessing the level of grain damage by elevating machinery, taking into account the geometric and kinematic parameters of their working bodies. Grain damage occurs as a result of several processes: impact collision of grain with the surfaces of the working bodies, due to friction of grain with each other and with the contact surface of the working bodies. In this case, the quantitative assessment of the level of grain damage for the selected processes can be considered using theory of probability. The essence of this description is to determine the general probability of preserving the integrity of the grain, taking into account the factors of influence. The general probability is determined by the product of the probability of no grain damage PP as a result of grain friction on the contact work surface, the probability Pv of grain preservation due to impact interaction with the elements of the working bodies and the probability Pℓ of no damage to the grain. Each separately determined probability is defined as an exponential function with a degree, which is formed through the kinematic and structural working bodies of elevating machinery. On the basis of the formed theoretical and probabilistic dependencies it is possible to outline the probable level of grain damage during transportation and implement various types of constructive modernization and im-provement of working bodies’ parameters of elevating machinery.